2020
DOI: 10.1111/cpr.12751
|View full text |Cite
|
Sign up to set email alerts
|

CCND1, NOP14 and DNMT3B are involved in miR‐502‐5p–mediated inhibition of cell migration and proliferation in bladder cancer

Abstract: Objectives Downregulation of miR‐502‐5p has emerged as a critical factor in tumour progression in several cancers. Herein, we elucidated the role of miR‐502‐5p in bladder cancer. Materials and methods RT‐qPCR was performed to examine the expression of miR‐502‐5p in bladder cancer. And DNA methylation analysis showed that epigenetic mechanisms may contribute to the downregulation of miR‐502‐5p. Then, wound‐healing assay, transwell assay, colony formation assay, CCK8 assay and flow cytometry analysis were applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 39 publications
(82 reference statements)
2
30
0
Order By: Relevance
“…On the other hand, some miRNAs have been documented to exert suppressing functions in BCs. miR-502-5p, for example, has been recently found to suppress the malignant behaviors of BCs cells through the different miRNA targets including CCND1, NOP14 and DNMT3B [21]. Similar trends have also been previously in miR-124-3p [22] and miR-203a [23].…”
Section: Discussionsupporting
confidence: 68%
“…On the other hand, some miRNAs have been documented to exert suppressing functions in BCs. miR-502-5p, for example, has been recently found to suppress the malignant behaviors of BCs cells through the different miRNA targets including CCND1, NOP14 and DNMT3B [21]. Similar trends have also been previously in miR-124-3p [22] and miR-203a [23].…”
Section: Discussionsupporting
confidence: 68%
“…On the other hand, some miRNAs have been documented to exert suppressing functions in BCa. miR-502-5p, for example, has been recently found to suppress the malignant behaviors of BCa cells through the different miRNA targets including CCND1, NOP14 and DNMT3B [ 23 ]. Similar trends have also been seen in miR-124-3p [ 24 ] and miR-203a [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that hsa_circ_0000231 was a sponge of miR-502-5p. It has been illustrated that miR-502-5p was indicated to inhibit cell proliferation and metastasis in bladder cancer and gastric cancer [12,13]. In breast cancer, miR-502-5p was downregulated and suppressed cell proliferation, whereas promoted cell apoptosis [26].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-502-5p is indicated to participate in cancer progression [ 9 11 ]. For example, miR-502-5p overexpression represses cell metastasis in bladder cancer [ 12 ]. MiR-502-5p is also indicated to regulate the tumorigenesis and metastasis of gastric cancer [ 13 ].…”
Section: Introductionmentioning
confidence: 99%